Correlations between Charpy V-notch impact energy and fracture toughness of nuclear reactor pressure vessel (RPV) steels. (October 2015) - Yu, Meifang; Luo, Zhen; Chao, Y.J.
Abstract: Correlations between Charpy V-notch (CVN) impact energy and fracture toughness are of great practical significance for reactor pressure vessel (RPV) structural integrity assessment. In this paper, correlations between the two for three commonly used RPV steels, namely Chinese A508-3 steel, USA A533B steel, Euro 20MnMoNi55 steel, are investigated with both a direct conversion and the Master Curve method. It is found that fracture toughness can be well predicted from CVN impact energy through reference temperature T 0 of the Master Curve method. Five predicted T 0 values from different correlations are close to the T 0 from actual test. The mean value of the five T 0 values provides a good estimate for the fracture toughness in the transition region.